Analysis of Multiphase Flow Centrifuge Decanter Separator Using CFD Simulations - Khogali, Ahmed (My University, 2022)
In the industry, it is common to encounter multiphase flow in many different applications in the oil and gas, food production and waste treatment industries. The nature of multiphase flow is extremely complex and is continuously developing in terms of methods and tools to perform analysis. One device in the industry involving mutiphase flow is the centrifuge decanter separator for sewage water treatment with the aim of separating fluid and solids. The centrifuge decanter in this study is a separator from Alfa Laval (AL). This study aims at analyzing the decanter by using computational fluid dynamics (CFD) as a simulation tool in combination with the field of multiphase flow modeling to understand the decanter’s different components and complex functions at high rotational speeds. This makes the decanter a very demanding topic for this type of research. The analysis of the phenomena was done through systematic changes in parameters, strategies and models. The Euler- Euler and Mixture multiphase models were used to predict the distribution of water and solids throughout the domain within the decanter separator and determine how efficient the separation process is in terms of the amount of exiting solids. Operation parameters such as the differential speed of the decanter parts and boundary conditions within the domain were analyzed and results were presented.
Keywords: CFD; Multiphase; Decanter; Separator; Mixture Model; Euler-Euler; Simulation; ANSYS